NILAI-NILAI RELIGIUS DALAM TINDAK TUTUR PADA PROSESI TEMU MANTEN UPACARA PERNIKAHAN ADAT JAWA DI KOTA MADIUN - Ardian Al Hidaya; Alfiati Alfiati; Khoirunnisaa' Khoirunnisaa' (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2016)
In general, this study aims to get a clear description of the events of speech acts in procession Temu Manten Javanese Traditional Wedding Ceremony containing prayers at every stage. The focus of this study include the stages of the procession Temu Manten, meaning each procession Temu Manten, and speech acts that occur at each stage of the procession Temu Manten containing prayers. This study was conducted over 6 months, in the City of Madison. Based on research problems that have been set, the design of the study is a qualitative research design. The study looked at every procession that held in Temu Manten, and seek information from several informants or sources that exist. Informants in this study are the Messiah Rias and Shaman Manten. Data collection techniques used in this research is interview, observation, recording technique, refer to the technical, and engineering notes, whereas the data analysis technique used is an interactive model. From the research findings related to the focus of the research results as follows: (1) the stages of the procession retrieval manten on Marriage Indigenous Java from three different locations in the City of Madison, all of them have a sequence of steps that together, (2) any procession Temu Manten has meaning that contain a request to Allah SWT (3) there is a non-verbal speech acts, namely the prayer said over the heart at any stage in the procession Temu Manten. Thus it can be concluded that there are religious values in the Speech Acts in procession Temu Manten Javanese Traditional Wedding Ceremony.